2018
DOI: 10.1002/cssc.201801757
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Utilization of Biomass Refinery Wastes for Accessing Activated Carbons and Supercapacitor Electrode Materials

Abstract: Biomass processing wastes (humins) are anticipated to become a large-tonnage solid waste in the near future, owing to the accelerated development of renewable technologies based on utilization of carbohydrates. In this work, the utility of humins as a feedstock for the production of activated carbon by various methods (pyrolysis, physical and chemical activation, or combined approaches) was evaluated. The obtained activated carbons were tested as potential electrode materials for supercapacitor applications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 82 publications
2
33
0
Order By: Relevance
“…Valorization toward materials applications has been suggested, and it was demonstrated that humins improve the mechanical properties of thermosetting composites. Recently, other products, such as humins‐derived porous materials and active carbon, have also emerged, with possible applications such as sorbents and electrode materials. Several humins treatment processes have also been proposed, such as hydrotreatment, oxidation, and pyrolysis .…”
Section: Introductionsupporting
confidence: 91%
“…Valorization toward materials applications has been suggested, and it was demonstrated that humins improve the mechanical properties of thermosetting composites. Recently, other products, such as humins‐derived porous materials and active carbon, have also emerged, with possible applications such as sorbents and electrode materials. Several humins treatment processes have also been proposed, such as hydrotreatment, oxidation, and pyrolysis .…”
Section: Introductionsupporting
confidence: 91%
“…The biochars were then applied as supercapacitor electrodes, and the electrochemical performances of as‐obtained biochar were tested by cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD) measurements (Figure c and Figure S7). The CV curves of electrodes made of thermally upgraded biochar (OH − ‐SR‐Biochar) showed non‐ideal rectangular shapes compared to traditional carbon‐based electrode materials, such as the OH − ‐SR‐Activated Biochar electrodes, which produced CV curves with more rectangular shapes. The non‐ideal behaviour can arise owing to the existence of some non‐active materials in the biochar .…”
Section: Resultsmentioning
confidence: 99%
“…Carbon‐based materials are widely used in supercapacitors as they possess high surface area and electrical conductivity, [ 6 ] and there are abundant inexpensive sources with low environmental impact, such as biomass refinery waste, [ 7 ] graphite pencil trace, [ 8 ] and widely available polymers such as polyimide. [ 9 ] For example, Lin et al showed that treating polyimide (Kapton) films using a commercial infrared CO 2 laser photothermally converts CO, CO, and NC bonds into sp 2 bonded carbon, with 2D graphene sheets randomly stacked along the c ‐axis, [ 10 ] termed as laser‐induced graphene or LIG.…”
Section: Introductionmentioning
confidence: 99%